Differential antibody response to COVID-19 disease and COVID-19 vaccines - Senol, Feray Ferda; Bahceci, Ilkay; Mercantepe, Filiz; Ibik, Yunus Emre; Suay Timurkaan, Esra; Toraman, Zulal Asci; Aytac, Ozlem; Oner, Pinar; Senol, Arzu (International Journal of Research in Medical Sciences, 2023)
Background: In our study, antibody positivity was evaluated by two methods in vaccinated and unvaccinated people according to their demographic characteristics and history of COVID-19. Methods: In this study, venous blood samples were taken from patients who were requested to have COVID-19 antibodies from our hospital’s outpatient clinics between February 2022 and March 2022. Results: There was no statistically significant difference when IgG antibody positivity was compared according to the age ranges in chemiluminescence and immunochromatographic methods. When patients were evaluated according to antibody titers, it was found that 81% of the seronegative patients were unvaccinated and had not had Covid-19, and it was found that this group was statistically significant compared to other groups. Conclusions: It has been concluded that it will be of great importance for every country, even every region, to have a test and vaccine policy for diagnosis and follow-up in the fight against COVID-19.